PIONEER VILLAGE 4.0: EMPOWERING MSME (MICRO, SMALL, AND MEDIUM ENTERPRISES) GROUPS THROUGH THE MYINNOVILLAGE PROGRAM IN BATU ROTO VILLAGE - Fadlurrohim, Ishak; Hila, Syahrio Marta (Sosiohumaniora, 2025)
Empowering MSME groups for a sustainable future is an initiative by the Onschool Indonesia Group aimed at enhancing the capacity of MSME actors, particularly women in Batu Roto Village, North Bengkulu Regency. This project utilizes digital technology to foster an inclusive and sustainable economic ecosystem. This study employs a descriptive quantitative approach. The sample consists of 70 members of the MSME group, including 11 men and 59 women. Data were collected through a Likert-scale questionnaire administered to members of the Batu Roto Village MSME group, whose businesses are primarily focused on the agricultural sector, as well as goods and service-based enterprises. The MSME empowerment strategy in Batu Roto Village demonstrates significant success in managerial and partnership dimensions. The synergy between entrepreneurship training and formal collaboration has effectively enhanced productivity and market resilience. However, the limited effectiveness in developing industrial centers and business sectors reveals a critical gap: individual capacity building remains suboptimal without adequate physical infrastructure support and continuous sectoral evaluation. Academically, this study contributes a “Hybrid Empowerment Model” that emphasizes social capital as a key driver in resource-constrained environments. The policy implications suggest a shift in the role of village governments—from mere providers of physical infrastructure to active facilitators of support services (IaaS). This includes conducting regular village innovation audits and institutionalizing MSME networks into legal cooperatives to strengthen their bargaining position within a more inclusive strategic partnership framework.